Physical activity self-management interventions for adults with spinal cord injury: Part 2 – Exploring the generalizability of findings from research to practice. (July 2018) - Burke, Shauna M.; Tomasone, Jennifer R.; Scime, Natalie V.; Ma, Jasmin K.; Harden, Samantha M.; Wolfe, Dalton L.
Abstract: Despite the benefits associated with regular participation in physical activity, individuals with spinal cord injury (SCI) remain insufficiently active. The ability to self-manage participation may increase physical activity levels, but only if self-management interventions can be implemented in the 'real world'. The purpose of this review was to examine the degree to which authors of published studies of LTPA self-management interventions for individuals with SCI have reported on factors that could increase the likelihood of translating this research into practice. A systematic search of five databases was conducted, yielding 33 eligible studies representing 31 interventions. Each intervention was assessed using the RE-AIM (Reach, Effectiveness, Adoption, Implementation, Maintenance) Framework and the PRECIS-2 (PRagmatic-Explanatory Continuum Indicator Summary) tool. The most commonly reported RE-AIM dimensions were Effectiveness (51.0% of interventions) and Reach (18.5%), followed by Implementation (14.2%), Maintenance (13.8%), and Adoption (4.0%). Overall, interventions were scored as primarily explanatory in five of the nine PRECIS-2 domains ( recruitment, primary analysis, organization, flexibility [delivery], follow-up ) and primarily pragmatic in one domain ( setting ). These findings suggest that while some LTPA self-management interventions for individuals with SCI are intended to be translated to real world settings, limited information is available to understand the degree to which this has been accomplished. Enhanced reporting of factors that could increase the likelihood of translating these interventions into practice is recommended. Highlights: Effectiveness was the most commonly reported RE-AIM dimension (51.0%). Some items within Adoption and Maintenance were not reported in any study. Lack of reporting on representativeness makes generalizability difficult. Interventions were scored as primarily pragmatic in only one PRECIS-2 domain ( setting ). Enhanced reporting is needed in this area to facilitate translation of research into practice.